El proceso monitorio en el nuevo código general del proceso (2016)
The investigation carried out before the monitoring process within the New General Code of the process includes an alternative to guarantee effective protection against the small obligations of money that the small shopkeepers stop charging and leave the void their rights, which is intended to demonstrate with The present work is the feasibility of starting this process before these situations of the day to day that guarantees its exigibility and is a solution to the relief of the judicial system focusing on the process and the use of the tests. Thus, it is pertinent to review the use of evidence in the monitoring process as a jurisdictional instrument, in light of the postulates proper to the Social State of Law, in order to claim its role as a judicial process that opens Space to the realization of the principles of good faith and due process